Dimensi Keibubapaan dalam Pendidikan Anak di Era Pandemik dan Solusi Menurut Kitab Manhaj Al-Tarbiah Al-Nabawiyyah li Al-Tifli - M Fariddudin, Siti Noor Farahin; Mohd Khambali @ Hambali, Khadijah; Syed Abdul Rahman, Syed Mohammad Hilmi Syed Abdul Rahman (Jurnal Usuluddin, 2022)
During the Covid-19 Pandemic, parents are facing conflicts in educating their children due to the new norms that have changed the lifestyles of people around the world. This pandemic has a profound impact on the development of the child especially emotionally and socially. Therefore, parents should master in parenting skills to help their children’s educational development. This study will present several dimensions of parenting skills in child education according to the book Manhaj al-Tarbiah al-Nabawiyyah li al-Tifli by Muhammad Suwaid. This study also discusses solutions in children’s education in the covid-19 pandemic. This study applies inductive and deductive methods by using thematic analysis. The results showed that the dimensions of faith, worship, social, emotional, moral, physical, intellectual, health and sexual are focused in this book. The dimensions of parenting skills discussed in this book are suitable as a guidance to assist parents in facing the challenges of their child’s education especially in the post-pandemic covid-19 era.